Seeing the supernatural : investigating angels, demons, mystical dreams, near-death encounters, and other mysteries of the unseen world - Strobel, Lee, 1952- (Zondervan Books, 2025)
"Discover solid biblical answers to the provocative questions you have been asking about the supernatural world--healings, angels, demons, mystical dreams, near-death experiences, heaven, hell, and more--through the investigative work of a former spiritual skeptic. We hear stories all the time about the supernatural--miraculous healings, unexplained sightings, near-death experiences--but how do we know what is real? Are rumors of spiritual beings, healings, and prophetic dreams dangerous deceptions, or is there something important for us to explore? Join investigative journalist and former atheist Lee Strobel as he examines the evidence and considers how we should think about the unseen world--and the God who made and rules over it...In Seeing the Supernatural, Lee weaves together his best material from several previous books with dynamic new and never-published interviews to investigate what the Bible really teaches about the unseen world.As he asks scholars the very questions you have about otherworldly experiences, Lee will help you: Better understand how God chooses to work in the fascinating supernatural realm--and why it is important, Avoid common mistakes people make, including both ignoring the supernatural and becoming obsessed with it, Have answers ready for when you face objections or deceptions that are common in a world of supernatural counterfeits, Draw closer to God as you catch glimpses of his power and glory in ways you don't typically experience. Written for skeptics and believers alike, Seeing the Supernatural is a transformative exploration of how the supernatural can shape our understanding of God's character and our own faith."--